Comparing thaw survival, implantation and live birth rates from cryopreserved zygotes, embryos and blastocysts - Mary Ellen Pavone; Joy Innes; Jennifer Hirshfeld-Cytron; Ralph Kazer; John Zhang (Wolters Kluwer Medknow Publications, 2011)
Context : Most in vitro fertilization (IVF) programs employ embryo cryopreservation to enhance pregnancies from a single ovarian stimulation. More embryos are created, some of which are not transferred to the uterus immediately, generating a need for improved cryopreservation protocols. One protocol may involve growing embryos to a further stage of development, allowing only embryos with proven developmental capabilities to be cryopreserved. Here we examined thaw survival, implantation and live birth rates of embryos cryopreserved at different stages. Aims : We examined thaw survival, implantation and live birth rates of embryos cryopreserved at the zygote, day 3 (D3) embryos or blastocyst stage. Settings and Design : This is a retrospective study from a single academic IVF program. Patients and Methods :0 A retrospective study of all patients who had frozen embryos transferred to their uteri from year 2002 to 2008 at a single academic IVF program was conducted. Statistical Analysis Used : Analysis of variance followed by Fisher's Exact Test was performed to compare the survival after thaw, implantation and live birth rates between the three groups. Results : One thousand nine hundred and ninety-one zygotes, 2880 D3 embryos and 503 blastocysts were frozen using a slow freeze technique, thawed and transferred. Significantly more D3 embryos and blastocysts survived the thawing process compared to zygotes and significantly higher implantation rate per number of thawed blastocysts was achieved than that for zygotes. Live birth rates were similar between the three groups. Conclusions : Growing embryos to blastocyst stage prior to cryopreservation is associated with fewer frozen embryos but does not appear compromise patients' chance of achieving pregnancy